Economic Aspects of Diversification of Farm Sector: A study of India - Singh, Nisha (Archives of Business Research, 2017)
The primary objective of this paper is to analyze the economic aspects of the landless, marginal and small farmers to surmise solutions on how they can able to supplement their income. To investigate this topic we refer to the world’s population and how it was doubled during the beginning of the twentieth century. For instant, in 1950 the population was 2.5 billion and now, in the year of 2016, it stands at 7.4 billion. By 2050 world population is projected to grow up to, approximately, 9 or 10 billion. Most of the growth is expected to occur in rural areas in developing countries, where the income elasticity demand for food remains high (Agricultural statics at a glance, Govt. of India, 2003). One of the top most populated and developing country is India where over two third of the population consist of farmers and their families. The food insecurity and malnutrition among children, women and men are due to the lack of purchasing power. ”